Srivijayan Buddhist Logic and Its Impact on the Malay Pantun - BOON CHUAN, TEE (Melayu: Jurnal Antarabangsa Dunia Melayu, 2020)
This paper aims to trace the origin of Malay pantun to the Buddhist logic of Srivijaya at the end of 7th century. Theoretical evidence from the records of Yi Jing (or I-Tsing,  635 CE-713 CE) shows that both Buddhist and public societies in Srivijaya were familiar with the genre of gātha (गाथ), a genre of Buddhist reasoning of Dharmakīrti (fl. 600 CE-650 CE) consisting of four lines comprising two units: thesis and reasons. Evidence from Srivijaya-era texts, i.e. from the Hastadaņda Śāstra (written by Śakyakīrti before 693 CE), have also shown traits that resemble the pantun that we know today. Therefore, the gātha-tradition of Srivijaya by the end of the 7th century is believed to have an impact of characterization to the origin of four lines with two pembayang (foreshadowers) and maksud (the purpose) units of Malay pantun in history. Keywords: logic, Buddhist, Srivijaya, Pantun, Malay